2018
DOI: 10.1038/s41598-018-36136-2
|View full text |Cite
|
Sign up to set email alerts
|

On the role of eye contact in gaze cueing

Abstract: Most experimental protocols examining joint attention with the gaze cueing paradigm are “observational” and “offline”, thereby not involving social interaction. We examined whether within a naturalistic online interaction, real-time eye contact influences the gaze cueing effect (GCE). We embedded gaze cueing in an interactive protocol with the iCub humanoid robot. This has the advantage of ecological validity combined with excellent experimental control. Critically, before averting the gaze, iCub either establ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
78
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 55 publications
(61 reference statements)
14
78
2
4
Order By: Relevance
“…Similar effects have been demonstrated with artificial agents [7,8]. As has been demonstrated before in other aspects of social cognition [9], embodiment seems to affect the social presence effect, as presence induced by images of social agents did not affect performance [10]. These studies, however, have used fairly simple tasks, such as arithmetic operations, that do not accurately resemble the complexity that characterizes practical applications of robots.…”
Section: Introductionsupporting
confidence: 71%
“…Similar effects have been demonstrated with artificial agents [7,8]. As has been demonstrated before in other aspects of social cognition [9], embodiment seems to affect the social presence effect, as presence induced by images of social agents did not affect performance [10]. These studies, however, have used fairly simple tasks, such as arithmetic operations, that do not accurately resemble the complexity that characterizes practical applications of robots.…”
Section: Introductionsupporting
confidence: 71%
“…This task was chosen for four reasons: First, attentional orienting to gaze signals is a social-cognitive process that is essential for human development and a prerequisite for higher-order social-cognitive processes, such as mentalizing [9,13,14]. Second, prior studies have shown that social attention is sensitive to the perceived social relevance of an interaction [10,12,[15][16][17][18][19], and specifically to the degree to which the gazer is perceived as having a mind [8,10,11,18]. Third, cognitive modeling of nonverbal signals like gaze cues in nonhuman agents has been a central topic for HRI since robots that display nonverbal signals can evoke natural responses from the interacting human [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Second, prior studies have shown that social attention is sensitive to the perceived social relevance of an interaction [10,12,[15][16][17][18][19], and specifically to the degree to which the gazer is perceived as having a mind [8,10,11,18]. Third, cognitive modeling of nonverbal signals like gaze cues in nonhuman agents has been a central topic for HRI since robots that display nonverbal signals can evoke natural responses from the interacting human [15,20,21]. Fourth, the paradigm allows for the simple manipulation of physical parameters of the gazer (i.e., humanlike vs. robot-like), behavioral parameters of the gaze signal (i.e., predictiveness and biological plausibility), and contextual parameters of the interaction (i.e., presence of reference objects and lifelikeness of the simulation).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, our results show that explicit subjective reports alone do not provide a comprehensive picture of cognitive mechanisms evoked by observation of (or interaction with) a robot. Objective measures are necessary to complement subjective reports by addressing specific, and often low-level implicit cognitive processes, an argument put forward in previous literature, due to a dissociation that has been observed between explicit and implicit measures [27]. Related to robot implementations directly, the differences we found in human attentional engagement, as well as a subjective impressions evoked by superficially similarly looking conditions hint that users' interaction with a robot can be qualitatively affected by subtle differences in its behavioral design.…”
Section: Discussionmentioning
confidence: 99%